The Effect of Grabfood Promotions, Service Quality, and Customers’ Expectations Towards Customers’ Satisfaction of PT. Grab Indonesia in Medan Class - Angella; Clara Nadia Yunan; Cynthia Honata; Ivy Joana; Winni Santoso (MultiTech Publisher, 2020)
PT. Grab Indonesia has provided an online-based transportation application for facilitating the customer to transport one place to another, in which this application offers services along with the promotions to the customers. As promotion and service quality are the important key to keep the customer satisfied and loyal to use grab services, there might be sometimes that grab does not provide as much promotion. The customers do have the expectation for the services that they are going to earn, especially if they are a loyal customer that always used the application, they will have higher expectations, then they will expect a lot of promotion as they always use, which should be a big consideration every time Grab plans a promotion. Customers’ decision of using Grabfood in Medan is often determined by the promotion that they get from the delivery platform. Satisfaction is often reached when the promotion offered meets their expectations